Origins of ductile plasticity in a polycrystalline gallium arsenide during scratching: MD simulation study - Fan, Pengfei; Goel, Saurav; Luo, Xichun; Yan, Yongda; Geng, Yanquan; He, Yang (Elsevier, 2021)
This paper used molecular dynamics simulation to reveal the origins of the ductile plasticity in polycrystalline gallium arsenide (GaAs) during its nanoscratching. Velocity-controlled nanoscratching tests were performed with a diamond tool to study the friction-induced deformation behaviour of polycrystalline GaAs. Cutting temperature, sub-surface damage depth, cutting stresses, the evolution of dislocations and the subsequent microstructural changes were extracted from the simulation. The simulated MD data indicated that the deformation of polycrystalline GaAs is accompanied by dislocation nucleation in the grain boundaries (GBs) leading to the initiation of plastic deformation. Furthermore, the 1/2〈1 1 0〉 is the main type of dislocation responsible for ductile plasticity in polycrystalline GaAs. The magnitude of cutting forces and the extent of sub-surface damage were both observed to reduce with an increase in the scratch velocity whereas the cutting temperature scaled with the cutting velocity. As for the depth of the scratch, an increase in its magnitude increased the cutting forces, temperature and damage-depth. A phenomenon of fluctuation from wave crests to wave troughs in the cutting forces was observed only during the cutting of polycrystalline GaAs and not during the cutting of single-crystal GaAs.
Keywords: Polycrystalline gallium arsenide; MD simulation; Grain boundary; Dislocation nucleation